2017
DOI: 10.1002/elps.201600430
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of single‐nucleotide polymorphisms by pyrosequencing with di‐base addition

Abstract: We have developed and validated a novel method for quantitative detection of SNPs by using pyrosequencing with di-base addition (PDBA). Based on the principle that the signal intensity is proportional to the template concentration within a linear concentration range, linear formula (Y = AX + B) for each genotype is established, and the relationship between two genotypes of a single SNP can be resolved by corresponding linear formulas. Here, PDBA assays were developed to detect variants rs6717546 and rs4148324,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…this technology is capable of detecting and quantifying allelic frequency to as low as ~5% [34]. We also concluded in our previous study that both read coverage and nucleotide frequency at a given position are significant for the SNV calling from NGS data and pyrosequencing confirmation [24].…”
Section: Resultssupporting
confidence: 62%
“…this technology is capable of detecting and quantifying allelic frequency to as low as ~5% [34]. We also concluded in our previous study that both read coverage and nucleotide frequency at a given position are significant for the SNV calling from NGS data and pyrosequencing confirmation [24].…”
Section: Resultssupporting
confidence: 62%
“…Our previous study revealed that an intra-host heterogeneity existed in virus-infected cultured cells detected by NGS and was confirmed with pyrosequencing [ 24 ]. Pyrosequencing methods are well-established and have proven suitable for SNV analysis and viral SNV identification [ 32 , 33 ]; this technology is capable of detecting and quantifying allelic frequency to as low as ~5% [ 34 ]. We also concluded in our previous study that both read coverage and nucleotide frequency at a given position are significant for the SNV calling from NGS data and pyrosequencing confirmation [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, in addition to ensuring the high depth of coverage for the SNVs, we employed both pyrosequencing and Illumina NGS for the SNV identification to combine both sequencing methods with complementary strengths. Pyrosequencing is a real-time sequencing method which is based on the detection of pyrophosphate released after each nucleotide incorporation in the new synthetic DNA strand, optimal for sequencing and analysis of short stretches of DNA, including SNPs [ 30 ], and has been intensively used for SNP detection since its emergence in 2005 [ 32 , 33 , 34 ]. Illumina NGS is one of the more recent sequencing technologies, it is massively parallel and allows millions of fragments to be sequenced in a single run, and it is currently used for wide applications including variation detection.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that biotin was attached to one of the DNA chains of the PCR fragment using the primer "bio-" (biotinylated). This was necessary for the analysis of the biotinylated DNA chain of the investigated amplificate using the pyrosequencing [35][36][37] . PCR primer sequences, taken for the present reseach [24,26,[28][29][30] Annealing temperature for the PCR is shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%